Osculating surfaces of curves on surfaces - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 2014)
Oosculating sphere have been studied in classical differential geometry [1]. In this article the osculating surfaces of higher order of space curves on surfaces in Euclidean space is considered. We study the intrinsic differential geometry of curves on surfaces by analyzing their contact with surfaces of higher order.